Avaliação da lombalgia, comprimento muscular e alterações na lordose lombar em corredores - Barbara Vendramini Marchetti; Bruna Lima Selau, Fernanda da Silva Medeiros; Claudia Tarragô Candotti (Universidade Estadual do Oeste do Paraná, 2015)
The aim of this study was to investigate if there is a relation between runners practice time and low back pain, muscle length and the posture of the lumbar spine, and identify if the practice time may influence the posture of the lumbar spine, hamstring muscle length and posterior muscles length. Thirty recreational runners divided in three groups (beginning, intermediate and advanced runners) were evaluated regarding to: the existence of low back pain,using a questionnaire; the hamstring muscle length, based on the range of motion (ROM) of hip flexion; the posterior muscles length, based on the distance between the fingers and the ground; and the angle of lumbar lordosis, using the flexicurve instrument. Data analyze ANOVA and simple correlation test of Spearman (p<.05). No significant correlations were found between the variables muscle length of hamstring, lumbar lordosis angle, complaints of lower back pain and posterior muscles length. It was found a significant correlation between the hamstring muscle length and posterior muscle length only for the intermediate group. The current study is in accordance with the literature, since several studies shown no consensus about the relationship between hamstring extensibility and low back pain, as well as complain of low back pain and the angle of lumbar lordosis. The running practice time do not have influence on muscle length of the posterior muscle and the hamstrings, as well as on lumbar spine posture.